2000
DOI: 10.1177/0170840600213003
|View full text |Cite
|
Sign up to set email alerts
|

Power, Control and Computer-Based Performance Monitoring: Repertoires, Resistance and Subjectivities

Abstract: This paper examines Computer-based Performance Monitoring (CBPM) in two UK financial services organizations. In doing so, it examines and critiques the existing manner in which this area has been theorized by both traditional and critical organization theorists. It then offers an alternative analysis of CBPM in terms of power, control and resistance, which involves the close interrogation of subject positioning within the speech of those who are subject to and manage this technology. By examining subject posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
121
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(126 citation statements)
references
References 16 publications
2
121
0
1
Order By: Relevance
“…Spicer's (2005) investigation of online innovations in an Australian public broadcaster found that various groups championed different representations of the technology in order to manipulate its organizational legitimacy. In a similar study of technological implementation, Ball and Wilson (2000) found that the use of stories and narratives was central to the agenda setting process. However, these stories and narratives may have broader structural consequences such as the marginalization of women in the organization.…”
Section: Manipulation 'In' Organizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spicer's (2005) investigation of online innovations in an Australian public broadcaster found that various groups championed different representations of the technology in order to manipulate its organizational legitimacy. In a similar study of technological implementation, Ball and Wilson (2000) found that the use of stories and narratives was central to the agenda setting process. However, these stories and narratives may have broader structural consequences such as the marginalization of women in the organization.…”
Section: Manipulation 'In' Organizationsmentioning
confidence: 99%
“…Because the spatial arrangement of the plant resembled a 'panopticon', the managerial gaze was always present among employees, to the extent where they enacted its influence upon themselves and fellow workers (also see Halford and Leonard, 2006). Knights and Murray's (1992) investigation of an insurance firm introducing new information systems similarly demonstrates how the new climate of 'transparency' substantially changed the way workers understood themselves and their roles, revealing the insidious social power of technology when enacted within certain political settings (also see Ball and Wilson, 2000;Coombs et al 2002;Bloomfield and Danieli 1995).…”
Section: Subjectification 'In' Organizationsmentioning
confidence: 99%
“…The culmination of discipline and punishment according to Foucault is the Panopticon, the process of surveillance and the internalisation of discipline. Although some scholars argue that the panoptic metaphor has been over-used (Ball and Wilson, 2000;Taylor and Bain, 2003;Thompson, 2003), it remains a useful concept to investigate processes of power and control in the education sector (e.g. Selwyn, 2000;Bushnell, 2003;Piro, 2008).…”
Section: External Accountabilitymentioning
confidence: 99%
“…Her er der snarere tale om en «flad» relation, hvor den overvågede ikke er fanget af overvågerens blik, men i stedet for bliver en aktør med egen dagsorden. Det kan eksempelvis vaere i form af modstand mod overvågerens blik (Ball & Wilson 2000;McGrath 2004), eller, som vi så ovenfor, kan det komme til udtryk på en mere positiv måde i form af «magtgivende ekshibitionisme» (Koskela 2004).…”
Section: Gensidighedunclassified